PRIMEIRO REGISTRO PARA O BRASIL DE Aphis Affinis DEL GUERCIO 1911 (HEMIPTERA: APHIDAE) - Silva, Carlos Roberto Sousa; Ilharco, F. A.; Pacheco, J. M. (REVISTA DE AGRICULTURA, 2015)
PRIMEIRO REGISTRO PARA O BRASIL DE Aphis Affinis DEL GUERCIO 1911 (HEMIPTERA: APHIDAE)